An online decision support system for inventory management. (20th February 2007) - Ho, G.T.S.; Lee, C.K.M.; Lau, H.C.W.; Ip, A.W.H.
Due to increasing popularity of using the Internet to perform businesses, enterprises are now facing tremendous pressure from competitors all over the world. In order to survive in the competitive marketplace, companies must be able to deliver their products at the right time, to the right place, and with the right price. Research studies have shown that decision support system can help enhancing the competitiveness of an enterprise. In general, decision support system technologies and applications are widely used by enterprises to support individual decision-makers, workgroups and virtual partners. This paper proposes a decision support system, which possesses certain intelligent features to support the inventory management. To validate the feasibility of the proposed system, a prototype system has been developed and installed in a local jewellery factory to support the inventory control, thereby helping the factory to maintain an optimal inventory level to match the market demand.